Mały ruch graniczny – konsekwencje dla regionów przygranicznych (Politeja, 2016)
Local border traffic at the Polish section of the European Union external border as a factor influencing the development of border regionsIt is in the interest of the European Union and Poland to ensure that the borders with its neighbors are not a barrier to trade, social and cultural interchange or regional cooperation. Such indication was included in the preamble of the Regulation No. 1931/2006 of the European Parliament and of the Council laying down rules on local border traffic at the external land borders of the Member States. The institution of local border traffic is very popular among the citizens of border areas. Thus – in the light of scale of the phenomenon – numerous questions arise: whether (in the economic dimension) the balance of the consequences of the implementation of the agreements on LBT is positive? Does an asymmetry of benefits take place, ie. the implementation of the agreement is more beneficial for one of its sides? Given the above views, the purpose of this article is the assessment of the economic consequences of its implementation (on the background of the prerequisite for the establishment of the LBT).